A comparison of socioeconomic status and mental health among inner-city Aboriginal and non-Aboriginal women. Issue 1 (1st January 2017) - Hamdullahpur, Kevin; Jacobs, Kahá:wi J.; Gill, Kathryn J.
ABSTRACT: Aboriginal women in urban areas have been reported to experience high rates of poverty, homelessness, interpersonal violence, and health problems. However, there are few prior ethnocultural comparisons of urban women from similar socioeconomic backgrounds. The current study explored the mental and physical health of Aboriginal and non-Aboriginal women accessing social services agencies and shelters. Half of the sample (n=172) was Aboriginal (48.3%). The lifetime rate of physical abuse was significantly higher in Aboriginal women, and they were more likely to have been victims of violence or crime in the past year (A=50.6%, NA=35.6%, p<0.05). Rates of teenage pregnancy (<18 years of age) were significantly higher among Aboriginals (A=51.3%, NA=30.6%, p<0.05) and they reported more parental drug/alcohol problems (A=79.2%, NA=56.5%, p<0.05). Aboriginal women were also more likely to have previously received treatment for a drug or alcohol problem. There were no differences in self-reported physical health, medication use, hospitalisations, and current substance misuse. Irrespective of ethnicity, lifetime rates of anxiety, depression and suicide attempts were extremely high. Future research should explore the effects of individual resources (e.g. social support, family relations) and cultural beliefs on women's ability to cope with the stress of living with adverse events, particularly among low SES women with children.